Electroacupuncture Regulates Disorders of Gut-Brain Interaction by Decreasing Corticotropin-Releasing Factor in a Rat Model of IBS - Ying Chen; Yan Zhao; Dan-ni Luo; Hui Zheng; Ying Li; Si-yuan Zhou (Gastroenterology Research and Practice)
Objective. Acupuncture is effective for irritable bowel syndrome (IBS); however, the mechanisms of action are not fully understood. We aim to explore the mechanism of electroacupuncture (EA) in the dual regulation of disorders of gut-brain interaction. Methods. A rat model of IBS was generated by chronic unpredictable mild stress (CUMS). Eight of 32 rats were assigned to the blank control group. The remaining 24 rats received CUMS for 14 days. Then, the rats surviving and successfully modelled were randomly divided into the CUMS group, the CUMS+EA group, and the CUMS+PB (pinaverium bromide) group. In the next 14 days of treatment, rats in the CUMS+EA group were acupunctured at ST25 (Tianshu), ST36 (Zusanli), SP6 (Sanyinjiao), and LR3 (Taichong) for 15 min every day. Rats in the CUMS+PB group were treated by the administration of gavage with 2.7 mg/mL pinaverium every day. Visceral pain threshold, the percentage of time spent in open arms (OT%) in the elevated plus maze test (EPMT), and the sucrose preference (SP%) in the sucrose preference test (SPT) were measured at baseline, day 15, and day 30. The expression of zonula occludens-1 (ZO-1), the morphology of the connective structure of intestinal epithelium, the CRF and CRF-R1 mRNA expression in the hypothalamus, and the double staining of intestinal mucosal mast cells (IMMC) and CRF-R1 were measured at the end of the experiment. Results. Compared with the blank control group, visceral pain threshold pressure, the expression of ZO-1, OT%, SP%, CRF, and CRF-R1 mRNA expression in the hypothalamus, and double staining of IMMC and CRF-R1 were decreased significantly in the CUMS group. Meanwhile, the morphology of the connective structure in the CUMS group was indistinct. Compared with the CUMS group, SP% was significantly increased in the CUMS+EA group, but there was no significant difference for it in the CUMS+PB group. The morphology of the connective structure in the two treatment groups was clear and seeable. And the expression of other parameters mentioned above was apparently increased in the two treatment groups. Compared with the CUMS+PB group, the expression of ZO-1 in the CUMS+EA group was significantly enhanced. And no obvious difference for other parameters was found between the two treatment groups. Conclusions. EA treatment can decrease the expression of hypothalamic CRF and CRF-R1, relieve anxiety and depression, meanwhile reduce the expression of CRF-R1 in the gastrointestinal mucosa, increase ZO-1 expression, and adjust tight junctions (TJs) to repair the intestinal mucosal barrier. The above roles suggest that EA may play a dual role in alleviating the gastrointestinal and psychological symptoms of IBS, suggesting a potentially dual therapeutic role for EA in regulating disorders of gut-brain interaction in IBS rats.